Benevolent leadership and its organisational outcomes: a social exchange theory perspective - Jue, Xin Tan; Zawawi, Dahlia; Abdul Aziz, Yuhanis (Faculty of Economics and Management, Universiti Putra Malaysia, 2016)
This study examines the relationship between benevolent leadership and employees’ organisational citizenship behaviour with organisational commitment as a mediator. Social exchange theory is applied in supporting the proposed relationship. A total of 163 employees from four- and fivestar hotels in the Klang Valley participated in the questionnaire survey. Structural Equation Modeling was employed to analyze the data and test the four hypotheses in this study. The empirical results show that there is a full mediation effect of organisational commitment on the relationship between benevolent leadership and organisational citizenship behaviour. Limitations of the study and directions for future research are suggested.